Handbook of Metalloproteins 2004
DOI: 10.1002/0470028637.met222
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate CarboxypeptidaseII

Abstract: Glutamate carboxypeptidase II (GCP II) is a homodimeric, dinuclear zinc carboxypeptidase that catalyzes the cleavage of two endogenous substrates carrying L ‐glutamate at the C‐terminal P1′ position, namely N ‐acetyl‐ L ‐aspartyl‐α‐ L ‐glutamate (α‐NAAG) and folylpoly‐γ‐ L ‐glutamate (folylpolyglutamate). Former synonyms for GCP II, a type‐II membrane glycoprotein that belongs to the transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…A comparison of CeGCP2.1 isoforms revealed that isoform CeGCP2.1b lacks the predicted intracellular domain. Isoform CeGCP2.1c completely lacks the C-terminal domain, which implies the loss or significant changes in the catalytic function, given that in its human homolog GCP2, the C-terminal domain is involved in substrate recognition [ 69 , 70 ]. No biological functions associated with these isoforms of GCP2.1 protein have been described so far, so we can only conclude homology to other isoforms and GCP2-like proteins of Caenorhabditis species, NAAG and transferrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of CeGCP2.1 isoforms revealed that isoform CeGCP2.1b lacks the predicted intracellular domain. Isoform CeGCP2.1c completely lacks the C-terminal domain, which implies the loss or significant changes in the catalytic function, given that in its human homolog GCP2, the C-terminal domain is involved in substrate recognition [ 69 , 70 ]. No biological functions associated with these isoforms of GCP2.1 protein have been described so far, so we can only conclude homology to other isoforms and GCP2-like proteins of Caenorhabditis species, NAAG and transferrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of CeGCP2.1 isoforms revealed that isoform CeGCP2.1b lacks the predicted intracellular domain. Isoform CeGCP2.1c completely lacks the C-terminal domain, which implies the loss or significant changes in the catalytic function, given that in its human homolog GCP2, the C-terminal domain is involved in substrate recognition (Barinka et al , 2007; Mesters & Hilgenfeld, 2008). No biological functions associated with these isoforms of GCP2.1 protein have been described so far, so we can only conclude homology to other isoforms and GCP2-like proteins of Caenorhabditis species, NAAG and transferrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…According DFT calculation-based studies, in transition state-1 (Figure 1), the hydrogen of the hydroxyl group of Glu24 is in the near-attack conformation and the Zn─Zn distance is elongated (from 3.3 A to 3.5 A). The carbonyl oxygen of the peptide bond is stabilised by Zn (1). Following the transition state-1, the system evolves towards the formation of the intermediate, which is structurally characterised by i) the elongated Zn─Zn distance, ii) a newly formed C─O bond between the oxygen atom of the bridging hydroxide and the carbon atom of the peptide bond of the substrate, iii) the stabilisation of the carbonyl oxygen of the substrate by Zn(1) and Tyr552, iv) the repositioning of the protonated hydroxyl group of Glu424 (Figure 1).…”
Section: Gcp II Structure and Reaction Mechanismmentioning
confidence: 99%
“…The type-II membrane glycoprotein glutamate carboxypeptidase II (EC 3.4.17.21), known as GCP II, is a homodimeric dinuclear zinc carboxypeptidase with the highest expression levels found in the nervous and prostatic tissue [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation